Mothering and welfare : depriving, surviving, thriving - Levasseur, Karine; Paterson, Stephanie, 1972-; Turnbull, Lorna A. (Demeter Press, 2020)
"This volume explores the intersections of welfare, gender and mothering work in the context of this political reality. It explores austerity and the policies of neoliberal governments that work to deprive some mothers of their welfare. This volume also explores how motherhood is socially constructed in various social locations and places around the world. Last, it examines different ways of thinking about mothering and what changes to laws and policies are required to assist all who are mothering and provide better support to their families."--